Ethnic minority women's experiences of accessing antenatal care in high income European countries: a systematic review - Esther Sharma; Pei-Ching Tseng; Angela Harden; Leah Li; Shuby Puthussery (BMC, 2023)
Abstract Background Women from ethnic minority backgrounds are at greater risk of adverse maternal outcomes. Antenatal care plays a crucial role in reducing risks of poor outcomes. The aim of this study was to identify, appraise, and synthesise the recent qualitative evidence on ethnic minority women's experiences of accessing antenatal care in high-income European countries, and to develop a novel conceptual framework for access based on women's perspectives. Methods We conducted a comprehensive search of seven electronic databases in addition to manual searches to identify all qualitative studies published between January 2010 and May 2021. Identified articles were screened in two stages against the inclusion criteria with titles and abstracts screened first followed by full-text screening. Included studies were quality appraised using the Critical Appraisal Skills Programme checklist and extracted data were synthesised using a 'best fit' framework, based on an existing theoretical model of health care access. Results A total of 30 studies were included in this review. Women's experiences covered two overarching themes: 'provision of antenatal care' and 'women's uptake of antenatal care'. The 'provision of antenatal care' theme included five sub-themes: promotion of antenatal care importance, making contact and getting to antenatal care, costs of antenatal care, interactions with antenatal care providers and models of antenatal care provision. The 'women's uptake of antenatal care' theme included seven sub-themes: delaying initiation of antenatal care, seeking antenatal care, help from others in accessing antenatal care, engaging with antenatal care, previous experiences of interacting with maternity services, ability to communicate, and immigration status. A novel conceptual model was developed from these themes. Conclusion The findings demonstrated the multifaceted and cyclical nature of initial and ongoing access to antenatal care for ethnic minority women. Structural and organisational factors played a significant role in women's ability to access antenatal care. Participants in majority of the included studies were women newly arrived in the host country, highlighting the need for research to be conducted across different generations of ethnic minority women taking into account the duration of stay in the host country where they accessed antenatal care. Protocol and registration The review protocol was registered on PROSPERO (reference number CRD42021238115).